1999
DOI: 10.1039/a906209b
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of selenium and tellurium in the presence of various modifiers in electrothermal atomic absorption spectrometry

Abstract: The behaviour of selenium and tellurium dissolved in nitric, hydrochloric or perchloric acid and in their mixtures was tested during the atomization process in a graphite tube with a platform. Palladium, magnesium nitrate and their mixture were used as the modi®ers. It was found that palladium is a good modi®er for selenium only in pure nitric or hydrochloric acid solutions. In perchloric acid and in all mixed media, selenium in the presence of palladium is lost almost completely during the evaporation and dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…A solution of 1,10-phenanthroline and thiosemicarbazide has been applied to suppress the effects of Cu, Pb, Ag, Au, Pt, Pd, and Se [9]. It was also found that the standard addition and successive dilution might be successfully used in the presence of Zn, Bi, Cd, and Pt [10]. Welz and SchubertJacobs [11] proposed the addition of Fe(III) in the presence of hydrochloric acid to eliminate the effects of copper, nickel, and silver.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A solution of 1,10-phenanthroline and thiosemicarbazide has been applied to suppress the effects of Cu, Pb, Ag, Au, Pt, Pd, and Se [9]. It was also found that the standard addition and successive dilution might be successfully used in the presence of Zn, Bi, Cd, and Pt [10]. Welz and SchubertJacobs [11] proposed the addition of Fe(III) in the presence of hydrochloric acid to eliminate the effects of copper, nickel, and silver.…”
Section: Introductionmentioning
confidence: 98%
“…Most pronounced are chemical interferences particularly those caused by elements that could simultaneously undergo reduction and form amalgams [9,10]. A solution of 1,10-phenanthroline and thiosemicarbazide has been applied to suppress the effects of Cu, Pb, Ag, Au, Pt, Pd, and Se [9].…”
Section: Introductionmentioning
confidence: 99%
“…MADRID et al [13] found that Cd(II) and Pb(II) do not interfere, although Se(IV), Ni(II) and Cu(II) depressed significantly the analytical signal of Hg. PSZOINCKI et al [10] investigated several ions and detected negative influence of Cu(II), Ag(I), Se(IV), Au(III), Pd(II) and Te(IV) on the analytical signal of Hg, at low concentrations. They used successfully the successive dilution method to eliminate these interferent effects.…”
Section: Interferencesmentioning
confidence: 99%
“…The CVAAS technique is based on the reduction of mercury compounds present in samples to free metal, followed by transformation of the metal into atomic vapour which is measured [10]. It seems, therefore, that this technique should be free from interferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation